The Efficiency of The Employees’ Performance in The Hospitality Services – Hotels and Resorts. In The Area of Koh Chang Trat Province. - Naekumdee, Narathip (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The purposes of this dissertation are: (1) to study factors that directly or indirectly affect workforce administration to increase the efficiency of the employees’ performance in the hospitality services - hotels and resorts in the area of Koh Chang Trat province. (2) to study directions the efficiency of the employees’ performance in the hospitality services - hotels and resorts in the area of Koh Chang Trat province The mixed methods research design was used. Quantitative data was collected from 400 samples including human resource managers, marketing managers, management managers, and assistant managers of each department. The data were analyzed by descriptive statistics such as Mean and Standard Deviation. Structural Equation Model (SEM) was used to verify the consistency of the model and the data. For qualitative research, in-depth interviews were conducted with 10 samples who were the owners or executives employed by the owners. The results from the analysis and interviews were discussed. The research found that: (1) Workforce administration to increase the efficiency of the hospitality industry was positively influenced by the following factors: Policy Managment (β = .465); Motivation (β = .461); Technology (β = .311). While Motivation was found to be casual factor (β = .254) that directly affected the efficiency of the employees’ performance. Policy Management (β = .455) and Technology (β = .331) directly affected the efficiency of the employees’ performance (β = .210) and Policy Management (β = .217) (2) In order to administrate workforce to increase the efficiency of the hospitality industry, the executives focus on the use of technology that is appropriate to the work of the organization. The meetings were held to collaboratively set up a plan and allowed everyone to get involved, exchange information, and create a corporate culture together taking into account of the customers’ satisfaction, both external and internal customers. The employees shall perform based on the facts in order to achieve a continuous improvement process in a standardized approach and reduce duplication of errors. This increases productivity indirectly. It also motivates employees to cooperate with the organization and to motivate them to work. Article history : Accepted 5 May 2017 SIMILARITY INDEX = 0.00